Association between use of novel glucose-lowering drugs and COVID-19 hospitalization and death in patients with type 2 diabetes: a nationwide registry analysis. Issue 1 (13th August 2022) - Ferrannini, Giulia; Lund, Lars H; Benson, Lina; Rizzo, Manfredi; Almahmeed, Wael; Rosano, Giuseppe M C; Savarese, Gianluigi; Cosentino, Francesco
Abstract: Aims: Type 2 diabetes (T2DM) in patients with coronavirus disease-19 (COVID-19) is associated with a worse prognosis. We separately investigated the associations between the use of sodium-glucose cotransporter 2 inhibitors (SGLT2i), glucagon-like peptide-1 receptor agonists (GLP-1 RA), and dipeptidyl peptidase-4 inhibitors (DPP-4i), and the risk of COVID-19 hospitalization and death. Methods and results: Patients with T2DM registered in the Swedish National Patient Registry and alive on 1 February 2020 were included. 'Incident severe COVID-19' was defined as the first hospitalization and/or death from COVID-19. A modified Poisson regression approach was applied to a 1:1 propensity score-matched population receiving vs. not receiving SGLT2i, GLP-1 RA, and DPP-4i to analyse the associations between their use and (I) incident severe COVID-19 and (II) risk of 30-day mortality in patients hospitalized for COVID-19. Among 344 413 patients, 39 172 (11%) were treated with SGLT2i, 34 290 (10%) with GLP-1 RA, and 53 044 (15%) with DPP-4i; 9538 (2.8%) had incident severe COVID-19 by 15 May 2021. SGLT2i and DPP-4i were associated with a 10% and 11% higher risk of incident severe COVID-19, respectively, whereas there was no association for GLP-1 RA. DPP-4i was also associated with a 10% higher 30-day mortality in patients hospitalized for COVID-19, whereas there was no association for SGLT2i and GLP-1 RA. Conclusion: SGLT2i and DPP-4i use were associated with a higher risk of incident severe COVID-19. DPP-4i use was associated with higher 30-day mortality in patients with COVID-19, whereas SGLT2i use was not. No increased risk for any outcome was observed with GLP-1 RA.